2022
DOI: 10.1038/s41573-021-00368-1
|View full text |Cite
|
Sign up to set email alerts
|

Immune targets for therapeutic development in depression: towards precision medicine

Abstract: Over the past two decades, compelling evidence has emerged indicating that immune mechanisms can contribute to the pathogenesis of major depressive disorder (MDD) and that drugs with primary immune targets can improve depressive symptoms. Patients with MDD are heterogeneous with respect to symptoms, treatment responses and biological correlates. Defining a narrower patient group based on biology could increase the treatment response rates in certain subgroups: a major advance in clinical psychiatry. For exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(97 citation statements)
references
References 194 publications
6
70
0
4
Order By: Relevance
“…Author details 1 Department of Chemical and Pharmaceutical Engineering, College of Chemical Engineering, Huaqiao University, Xiamen 361021, Fujian province, People's Republic of China. 2 Research Center of Natural Resources of Chinese Medicinal Materials and Ethnic Medicine, Jiangxi University of Chinese Medicine, Nanchang 330004, Jiangxi province, People's Republic of China. 3 Xiamen Hospital of Traditional Chinese Medicine, Xiamen 361009, Fujian province, People's Republic of China.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Author details 1 Department of Chemical and Pharmaceutical Engineering, College of Chemical Engineering, Huaqiao University, Xiamen 361021, Fujian province, People's Republic of China. 2 Research Center of Natural Resources of Chinese Medicinal Materials and Ethnic Medicine, Jiangxi University of Chinese Medicine, Nanchang 330004, Jiangxi province, People's Republic of China. 3 Xiamen Hospital of Traditional Chinese Medicine, Xiamen 361009, Fujian province, People's Republic of China.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Recently, increasing evidence has shown that neuroimmune is a key factor that correlates with major depression [2]. Complement system participates in both innate immunity and adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-cytokine therapies have been recently cornered as potential strategies for decreasing MDD symptoms severity, although they have been mostly investigated in patients with severe, chronic organic diseases, where the mood manifestations were not the center of clinical attention, but associated features ( Drevets et al, 2022 ). There is overwhelming evidence that immune dysregulation is frequently associated with depression, and MDD has been associated with elevated levels of pro-inflammatory cytokines and acute-phase proteins both in the central nervous system and in the blood, but also with decreased adaptive immune response, a bias toward autoimmunity, and other immune changes ( Drevets et al, 2022 ). The effects of anti-cytokine therapies as adjunctive agents in patients with treatment-resistant MDD or bipolar depression have been investigated in clinical trials, with mixed results ( Drevets et al, 2022 ).…”
Section: Anti-inflammatory Therapies As Potential Treatments For Depr...mentioning
confidence: 99%
“…There is overwhelming evidence that immune dysregulation is frequently associated with depression, and MDD has been associated with elevated levels of pro-inflammatory cytokines and acute-phase proteins both in the central nervous system and in the blood, but also with decreased adaptive immune response, a bias toward autoimmunity, and other immune changes ( Drevets et al, 2022 ). The effects of anti-cytokine therapies as adjunctive agents in patients with treatment-resistant MDD or bipolar depression have been investigated in clinical trials, with mixed results ( Drevets et al, 2022 ).…”
Section: Anti-inflammatory Therapies As Potential Treatments For Depr...mentioning
confidence: 99%
“…This evidence includes: (1) Depression is often accompanied by increased neuroinflammation ( 68 ). In the CNS, increased pro-inflammatory cytokines, which may come from the periphery or be produced from cells within the CNS, and activation of microglia as the resident immune cells of the brain are observed in MDD by imaging and post-mortem studies ( 69 – 73 ). (2) The central administration of exogenous inflammatory irritants can induce depressive symptoms ( 74 , 75 ).…”
Section: Possible Anti-depressant Mechanisms Of Action Of Omega-3 Pufasmentioning
confidence: 99%